Frida Kahlo as a Symbol of Mexican National Identity (some thoughts after a theatre performance) - A. V. Rodionov (Ибероамериканские тетради)
The scholars keep on searching for a definition of a «national identity» concept, while many states are trying to understand the essence of their national identity, and Latin American countries are no exception. The states reconsider their attitudes towards their own history, their cultural roots. The Mexican artist Frida Kahlo has become a world-famous brand: books and articles are written about her, plays and ballets are dedicated to her, her image is placed on bags and clothes. Frida’s popularity can be explained by her peculiar painting style, which absorbed the key elements of national culture and reflected the Mexican people’s character. At the same time, not only did Frida absorb and vividly reflect the national identity of the country, but she herself also became a symbol, a myth of Mexico for both the Mexicans, and for the outside world. Frida Kahlo’s paintings represent various elements of the Mexican style of life, namely retablo, the national costume, Mexico’s nature, and the traditional beliefs and customs of the Indian peoples. Frida was a borderline painter: she looked forward, fighting for equality, for women’s rights, she was a member of the Communist Party; whereas as an artist, though using new, revolutionary forms of painting, she looked back to the history and traditions of her country.